39.6k views
2 votes
Which is the correct answer?

Note: ( if you give me a silly or absurd answer I will report you)​

Which is the correct answer? Note: ( if you give me a silly or absurd answer I will-example-1
User SHRI
by
4.9k points

1 Answer

5 votes

Explanation:

y = x² - 16

x² = y + 16

x = sqrt(y + 16) because x is non-negative.

Hence the inverse function is f^(-1)(x) = sqrt(x + 16). (A)

User Rj Tubera
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.